2021
DOI: 10.3390/ijms22147755
|View full text |Cite
|
Sign up to set email alerts
|

Microbeam Radiotherapy—A Novel Therapeutic Approach to Overcome Radioresistance and Enhance Anti-Tumour Response in Melanoma

Abstract: Melanoma is the deadliest type of skin cancer, due to its invasiveness and limited treatment efficacy. The main therapy for primary melanoma and solitary organ metastases is wide excision. Adjuvant therapy, such as chemotherapy and targeted therapies are mainly used for disseminated disease. Radiotherapy (RT) is a powerful treatment option used in more than 50% of cancer patients, however, conventional RT alone is unable to eradicate melanoma. Its general radioresistance is attributed to overexpression of repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…Only the following two in vivo tumor models have been studied for comprehensive transcriptomic analysis after MRT: EMT6.5, a mouse breast cancer model, and 9L rat orthotopic glioblastoma [ 16 , 18 ]. In a very recent review, Trappetti et al performed a comparative gene expression analysis between these two studies [ 41 ]. Interestingly enough, CXCL9 was one of two candidates for the unique gene signature of MRT.…”
Section: Discussionmentioning
confidence: 99%
“…Only the following two in vivo tumor models have been studied for comprehensive transcriptomic analysis after MRT: EMT6.5, a mouse breast cancer model, and 9L rat orthotopic glioblastoma [ 16 , 18 ]. In a very recent review, Trappetti et al performed a comparative gene expression analysis between these two studies [ 41 ]. Interestingly enough, CXCL9 was one of two candidates for the unique gene signature of MRT.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from several preclinical studies using various animal models reported that the highly heterogenous dose deposition achieved with SFRT is associated with a superior immunological response in tumour tissue [ 24 , 25 ]. Tumour cell ablation from areas of peak dose is thought to discharge tumour antigen material that enables dendritic priming of T-cells.…”
Section: Molecular and Radiobiological Mechanisms Of Spatially Fracti...mentioning
confidence: 99%
“…Overexpression of genes after MRT (including Ccl9 and the human leukocyte antigen gene complex (HLA) family members responsible for encoding the major histocompatibility complex (MHC) Class II. Ccl9 expression) is responsible for the CCL9 chemokine known to recruit immune cells to tumour sites and also found to have an immunological role in signalling antileukemic responses [ 25 , 29 ]. Importantly, these transcriptomic studies give evidence of different genetic pathways of response to radiation exposure, dependent on MRT or conventional broad beam irradiation, suggesting a possible biological mechanism behind the greater efficacy observed in tumour control with SFRT.…”
Section: Molecular and Radiobiological Mechanisms Of Spatially Fracti...mentioning
confidence: 99%
“…Another compelling hypothesis for the efficacy of SFRT involves the immune system. Several studies demonstrated a role of the immune system in the tumour response towards SFRT treatments (Bouchet et al 2013 , Yang et al 2019 , Trappetti et al 2021 ). It is well known that radiation therapy possesses immune stimulating effects (Formenti and Demaria 2013 , Vatner et al 2014 ), but it usually does not suffice to disrupt the immune tolerance against the tumour.…”
Section: Spatially Fractionated Beams: Cell and Tissue Effects Toward...mentioning
confidence: 99%